Managerial Effectiveness I: Formulating a Research Strategy - Cummings, L. L. (Academy of Management Journal, 1966)
This is the first of a series of papers designed to report the various stages of a longitudinal research project on the study of managerial effectiveness. The purposes of this article are: (1) to set forth the various dimensions of the overall research effort; (2) to present a review of the research on the prediction of managerial success or effectiveness; and, (3) to establish the focus for a second paper subsequently to appear in the Academy of Management Journal describing the results and implications of an intermediate research effort.